Use of chlorine dioxide fumigation to alleviate enzymatic browning of harvested 'Daw' longan pericarp during storage under ambient conditions - Kobkiat Saengnil (2018)
Pericarp browning reduces both the shelf-life and market value of harvested longan fruit stored at room temperature. Our study investigated the efficiency of chlorine dioxide (ClO 2 ) fumigation at reducing pericarp browning of longan (Dimocarpus longan Lour.) cv. Daw. Fresh longan fruit were fumigated with 0 (control), 2.5, 5, 10 and 25mg/L ClO 2 for 10min, before being packed in cardboard boxes, and stored at 25±1°C, RH 82±5% for 7 days. Fruit treated with ClO 2 had a lower browning index, but higher hue angle (true color), L* (lightness) and b* (yellowness) values than non-treated fruit. The 10 and 25mg/L ClO 2 treatments were the most effective at extending shelf-life from 1 to 5 days, compared with the control, by reducing pericarp browning, the activities of polyphenol oxidase (PPO) and peroxidase (POD), disease development and by maintaining the highest total phenolic content. However, quality acceptance of fruit treated with 10mg/L ClO 2 was higher than fruits treated with 25mg/L, as determined by odor and flavo r. Consequently, ClO 2 fumigation at a concentration of 10mg/L was considered to be the most effective treatment to reduce pericarp browning of longan, whilst maintaining fruit quality. © 2014 Elsevier B.V.